ANALISIS SWOT STRATEGI PEMASARAN PRODUK TABUNGAN EMAS DI PT. PEGADAIAN DALAM UPAYA MENINGKATKAN JUMLAH NASABAH (STUDI KASUS PT. PEGADAIAN KANTOR AREA JEMBER) - Pradista, Dyah Alfiani; Hafidzi, Achmad Hasan; Reskiputri, Tatit Diansari (Growth, 2022)
This study aims to formulate a marketing strategy for gold savings products at pawnshops in an effort to increase the number of customers (study at PT. Pegadaian Jember Area Office). Analysis of the data used in this study is a SWOT (Strength, Weakness, Opportunity, Treath) matrix. This study uses a descriptive type of research with a qualitative approach, which is a research method used to examine the condition of natural objects. The results of this study indicate that the IFAS matrix analysis has a total score of 1.244, the total score of the EFAS matrix is 1.645. On the results of these calculations PT. Pegadaian Jember Area Office is in quadrant 1 which means that the situation is very profitable for the company in carrying out an aggressive strategy or growth. From the results of research on alternative strategies for gold savings products that have been obtained and practical researchers to determine the marketing strategy of PT. Pegadaian Jember Area Office, increasing targeted promotions, developing innovations in gold savings products, conducting socialization about gold savings products, as well as formally cooperating with gold shops in the market